Brain lipid sensing and the neural control of energy balance. (15th December 2015) - Magnan, Christophe; Levin, Barry E.; Luquet, Serge
Abstract: Fatty acid (FA) -sensitive neurons are present in the brain, especially the hypothalamus, and play a key role in the neural control of energy and glucose homeostasis including feeding behavior, secretion insulin and action. Subpopulations of neurons in the arcuate and ventromedial hypothalamic nuclei are selectively either activated or inhibited by FA. Molecular effectors of these FA effects include ion channels such as chloride, potassium or calcium. In addition, at least half of the responses in the hypothalamic ventromedial FA neurons are mediated through interaction with the FA translocator/receptor, FAT/CD36, that does not require metabolism to activate intracellular signaling downstream. Recently, an important role of lipoprotein lipase in FA detection has also been demonstrated not only in the hypothalamus, but also in the hippocampus and striatum. Finally, FA could overload energy homeostasis via increased hypothalamic ceramide synthesis which could, in turn, contribute to the pathogenesis of diabetes of obesity and/or type 2 in predisposed individuals by disrupting the endocrine signaling pathways of insulin and/or leptin. Highlights: Hypothalamic fatty acid sensing is involved in regulation of food intake, insulin secretion and action. FAT/CD36 is a key actor of hypothalamic fatty acid sensing. Fatty acid sensing may also regulate reward circuitry.